Desenvolvimento e avaliação de um programa interventivo para promoção de funções executivas em crianças - Dias, Natália Martins (2013)
Executive functions (EF) are a set of cognitive and metacognitive processes fundamental to the control and regulation of behavior, emotion and cognition. International studies have emphasized the importance of these functions to learning and self-regulated behavior and designed intervention programs to promote the development of these skills. However, the same emphasis has not occurred nationally. This project aims to (1) develop the Early Intervention Program on Executive Functioning (PIAFEx) and (2) to test its efficacy in a sample of children. In the first part of the study, we developed the program activities and the same was submitted to the judges. A subsequent review led to the final version of the PIAFEx, which has 42 activities divided into 10 basic modules and a supplement. Their activities provide opportunity in which children can practice adaptive and self-regulated behaviors in a variety of situations and contexts. In the second part of the study, the final sample consisted of 138 children of preschool and 1st year of elementary school, with an average age of 5.5 years, enrolled in two public schools in the state of SP. Besides children, 10 teachers participated, five of preschool classes and five of 1st grade. Of these, four classes (two from each grade level) constituted the experimental group (EG) and six classes (three from each grade level), the Control Group (CG). The PIAFEx was implemented and evaluated over three stages: pretest, intervention and posttest. In the pretest, all children were assessed at Simon Task, Semantic Stroop Test, Trail Making Test for preschoolers, Columbia Mental Maturity Scale (CMMS) and Peabody Picture Vocabulary Test. Parents and teachers responded to the Children Executive Functioning Inventory (CHEXI) and questionnaires (QPA for parents and QPR for teachers) about child and teacher s basic informations. In the intervention stage, the teachers of GE were instructed and supervised in the implementation of the activities of the PIAFEx. The teachers conducted the activities daily in the classroom. The GC remained with the regular activities. At posttest, the same procedure of the pretest was repeated, except for the EMMC and questionnaires QPR and QPA, and an interview was performed with the EG teachers. ANCOVAs were conducted, with each performance index of each instrument in the posttest as the dependent variable and the same performance in the pretest as covariate, separately for each grade level. The analyzes showed gains of the intervention on performance in attention and inhibition, measured by performance tests, for preschool children and on attention, inhibition and cognitive flexibility, measured by performance tests, and planning and working memory, as measured by CHEXI for children from 1st grade. There were gains in vocabulary skill only to EG from 1st grade and no gain on the naming speed, as expected since the intervention did not aim to develop such skill. Regression analyzes showed that socioeconomic, family and school / teacher variables contribute to the development of cognitive flexibility skills, even only individual variables figured as predictors of measures of inhibition. These analyzes also suggest that participation in the intervention may outweigh the effects of socioeconomic, family and school / teacher variables, confirming the effects of the intervention evidenced from ANCOVAs. A content analysis of the interviews with the teachers of the EG showed their perceptions of gains in organizational skills, planning, discipline, interaction and conflict resolution among children. The study enabled the development and contributes to providing an unprecedented intervention procedure in Brazil. Furthermore, the research showed its applicability in different grade levels and its effectiveness in promoting the development of EF in preschoolers and children in early elementary school, promoting fruitful contributions to the dialogue between neuropsychology and education, from a preventive view.